Implementation of the Literacy Program: A case stady at the SD 006 Bangsal Aceh, Dumai City - Nelsy, Asma; Mahdum, Mahdum; Saam, Zulfan (Journal of Educational Sciences, 2022)
The development of education and culture is directed at improving the quality of life. The State Elementary School 006 (SD 006) Bangsal Aceh takes part in the government program, namely the National Literacy Movement. In response to this, the researchers observed for approximately five years the iteration program at this school was running. This study aims to describe on how to implement of the literacy program, the obstacles and solutions that are carried out in the implementation of the literacy program, the relationship between students' reading interest and the implementation of the literacy program, and the relationship between students' interest in writing for students with the implementation of literacy programs. This study used a qualitative approach with a descriptive type. Sources of research data were the principal, 5 teachers, and 4 students. Data collection techniques used the Miles and Huberman models. Test the validity of the data used technical triangulation and source triangulation. The results of the study indicate that the implementation of the program has not been realized properly. The obstacles to implementing the program are a less supportive environment, incomplete infrastructure, unliterate parents, and lack of examples of teachers in literacy habituation in schools. Students' reading and writing interest are still low.